Molecular structure retrieval directly from laboratory-frame photoelectron spectra in laser-induced electron diffraction - A. Sanchez (Nature Portfolio, 2021)
Optical methods utilizing ultrashort laser pulses are commonly used to probe structure and dynamics of atoms and molecules. Here the authors report a method which uses critical points and is capable of extracting molecular structure with picometer spatial and attosecond temporal resolution.